2005
DOI: 10.1016/j.femsec.2004.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of nitric oxide reductase gene homologues from aerobic ammonia-oxidizing bacteria

Abstract: Nitric oxide (NO) and nitrous oxide (N2O) are climatically important trace gases that are produced by both nitrifying and denitrifying bacteria. In the denitrification pathway, N2O is produced from nitric oxide (NO) by the enzyme nitric oxide reductase (NOR). The ammonia-oxidizing bacterium Nitrosomonas europaea also possesses a functional nitric oxide reductase, which was shown recently to serve a unique function. In this study, sequences homologous to the large subunit of nitric oxide reductase (norB) were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 46 publications
(74 reference statements)
2
52
0
Order By: Relevance
“…The distribution of the radiatively active trace gas nitrous oxide (N 2 O) may also be strongly influenced by these organisms: AOB (Casciotti and Ward, 2005), denitrifiers, and now AOA (Hallam et al, 2006b) possess nitric oxide reductase (nor) genes that could be involved in N 2 O production. Anammox bacteria are now known to produce N 2 O as well (Kartal et al, 2007a) -not as an intermediate of the anammox reaction but apparently as a result of NO detoxification.…”
Section: New Paradigmsmentioning
confidence: 99%
“…The distribution of the radiatively active trace gas nitrous oxide (N 2 O) may also be strongly influenced by these organisms: AOB (Casciotti and Ward, 2005), denitrifiers, and now AOA (Hallam et al, 2006b) possess nitric oxide reductase (nor) genes that could be involved in N 2 O production. Anammox bacteria are now known to produce N 2 O as well (Kartal et al, 2007a) -not as an intermediate of the anammox reaction but apparently as a result of NO detoxification.…”
Section: New Paradigmsmentioning
confidence: 99%
“…The other mechanism, known as nitrifier-denitrification, is the sequential reduction of NO − 2 to NO and then N 2 O by the action of the nitrite reductase (NIR, encoded by the gene nirK) and the nitric oxide reductase (NOR, encoded by the gene norB). All of the ammoniaoxidizing bacteria that have been screened to date contain the nirK and norB genes (Casciotti and Ward, 2001;Shaw et al, 2006;Casciotti and Ward, 2005;Cantera and Stein, 2007;Norton et al, 2008;Arp et al, 2007), and the conversion of 15 NO − 2 to 15 N 2 O has been demonstrated in several genera (Poth and Focht, 1985;Shaw et al, 2006). Archaeal ammonia oxidizers also appear to possess nirK and norB homologs (Treusch et al, 2005;Hallam et al, 2006;Walker et al, 2010) but it is not known whether the proteins encoded by these genes are involved in N 2 O production.…”
mentioning
confidence: 99%
“…S6 and Table S1 in the supplemental material). We acknowledge that the high specificity of reverse transcription (RT)-PCR assays may fail to detect related mRNA targets (in this case, expressed bacterial nirK and norB); nonetheless, the assay is broadly accepted as state of the art for assessing expression of genes involved in N 2 O production by denitrification pathways (11,15). Thus, we have assembled four independent lines of evidence that argue against the possibility that minor denitrifying bacterial populations in the enrichment are responsible for N 2 O production in the strain MY1 culture: (i) assays were clearly aerobic (ammonia oxidation and N 2 O production were impaired at reduced O 2 [see above]), (ii) the AFM had only NH 3 as an electron donor, (iii) an ammonia oxidation inhibitor (which does not inhibit denitrification) completely inhibited the production N 2 O, and (iv) neither of the two bacterial genes that might potentially participate in N 2 O production by Bacteria present in the coculture was expressed.…”
mentioning
confidence: 99%